Location-Based Information Systems Developing Real-Time Tracking Applications - Labrador, Miguel A. (Taylor & Francis, 2010)
Drawing on the authors' more than six years of R&D in location-based information systems as well as their participation in defining the Java ME Location API 2.0, this text describes the technical components needed to create location-based services with an emphasis on nonproprietary, freely available solutions that work across different technologies and platforms. Each chapter presents a general real-time tracking system example that can be easily adapted to target any application domain and that can incorporate other sensor data to make the system "participatory sensing" or "human-centric sensing." A companion website offers many supporting materials.